Return Predictability in Laboratory Asset Markets. Issue 4 (28th November 2022) - Cheng, Zhongming; Lin, Shengle
Abstract: Empirical studies find that the order imbalance of retail trades can predict future stock returns. The authors investigated the cause of the puzzle using data from the laboratory asset markets in which inexperienced subjects trade in a single asset market (SSW design). The authors found that the retail order imbalance in period t positively predicted returns in period t + 1 in laboratory markets. The existence of return predictability in laboratory markets in which insider information or institutional investors are absent suggests that the predictability is not contingent upon private information or the activities of institutional investors, thus diminishing support of theories relying on these 2 conditions. In addition, the authors found that the return predictability in lab results was stronger and more statistically significant when the subjects were more excited. They tested this novel lab finding in empirical data and confirmed that return predictability is more robust when the market sentiment is higher. The findings suggest that the cause of the return predictability is likely linked to speculative activities.